2017
DOI: 10.1016/j.devcel.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The Conserved Intron Binding Protein EMB-4 Plays Differential Roles in Germline Small RNA Pathways of C. elegans

Abstract: Proper regulation of the germline transcriptome is essential for fertility. In C. elegans, germline homeostasis hinges on a complex repertoire of both silencing and activating small RNA pathways, along with RNA processing. However, our understanding of how fundamental RNA processing steps intersect with small RNA machineries in the germline remains limited. Here, we link the conserved intron binding protein, EMB-4/AQR/IBP160, to the CSR-1 and HRDE-1 nuclear 22G-RNA pathways in the C. elegans germline. Loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…The human ortholog Aquarius is an RNA helicase with ATPase activity, and it binds to introns to assist intron splicing in vitro (Hirose et al, 2006;De et al, 2015). The C. elegans ortholog EMB-4 was reported to act in the nuclear RNAi pathway, where it interacts with nuclear AGOs and functions in germline-specific chromatin remodeling (Checchi and Kelly, 2006;Akay et al, 2017;Tyc et al, 2017). In Arabidopsis, MAC7 is involved in plant defense and was predicted to be an essential gene (Tzafrir et al, 2004;Monaghan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human ortholog Aquarius is an RNA helicase with ATPase activity, and it binds to introns to assist intron splicing in vitro (Hirose et al, 2006;De et al, 2015). The C. elegans ortholog EMB-4 was reported to act in the nuclear RNAi pathway, where it interacts with nuclear AGOs and functions in germline-specific chromatin remodeling (Checchi and Kelly, 2006;Akay et al, 2017;Tyc et al, 2017). In Arabidopsis, MAC7 is involved in plant defense and was predicted to be an essential gene (Tzafrir et al, 2004;Monaghan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications show that EMB-4, the Caenorhabditis elegans homolog of MAC7, physically interacts with germline AGOs. It participates in the nuclear RNAi pathway and maintains the homeostasis of germline transcriptome in worms (Akay et al, 2017;Tyc et al, 2017). MAC7 was predicted to be an essential gene for embryo development (EMB gene) in Arabidopsis based on sequence similarity with EMB genes found in other eukaryotes (Tzafrir et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that nuclear RNA accumulation of the endogenous HRDE-1 targets may reflect aberrant structures or deficiencies in RNA-processing of these transcripts. Such connections have been found in S. pombe [41,42] and recently in C. elegans [43,44]. Investigating the cause of the nuclear enrichment will provide insights into the triggering mechanism of nuclear RNAi in C. elegans.…”
Section: Is Nuclear Accumulation a Sign Of "Foreign"?mentioning
confidence: 68%
“…On the contrary, a significant depletion was found for genes known to be targeted by CSR-1-carried small RNAs, a pathway that was suggested to support the expression of targeted genes (Claycomb et al, 2009;Shen et al, 2018). The helicase EMB-4 (Akay et al, 2017;Tyc et al, 2017) was shown to preferably bind introns of genes targeted by CSR-1; We could not detect a significant enrichment or depletion for genes whose introns are bound by EMB-4. All together, these results suggest that SET-25 is required for the maintenance of a specific sub-class of HRDE-1 and WAGO-1 small RNAs, associated with the Mutator and piRNA pathways, which target protein-coding ( Figure S2).…”
Section: Set-25 Is Required For the Maintenance Of A Specific Class Omentioning
confidence: 99%